(untitled) (Journal of Applied Learning and Teaching, 2025)
This research investigates the digital divide among undergraduate students across various demographic backgrounds at UK universities, focusing on the progression of this gap over three academic years. Through the theoretical lens of connectivism and analyzing data from 595 students in two business schools via a survey, this study explores the disparity in digital literacy between widening and non-widening participants between domestic and international students. Our findings indicate that Year 2 students display peak confidence in their digital abilities, which notably declines by Year 3. The digital divide between widening participants and their counterparts progressively exacerbates throughout the undergraduate journey. Distinctly, the division between home and international students is highlighted by their proficiency in particular digital skills, where each group excels in specific areas. Furthermore, we observe that formal educational resources do not meet the diverse needs of all student groups, thus potentially broadening the digital divide. In contrast, widening participants and international students often resort to online resources over traditional educational support. Drawing on these insights, we advocate for strategies that include continuous self-assessment, tailored support, and adaptability enhancement to bridge this digital divide and advance inclusive education.